GEODYNAMIC PROCESSES ON THE SHORE OF RESERVOIRS OF HYDROELECTRIC POWER STATIONS OF THE CANYONS TYPE IN THE REPUBLIC OF BELARUS (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Design and construction of modern hydraulic structures, which include a hydroelectric power station, dam, shipping lock, earth dam, reservoir, etc., require detailed forecasting of their impact on adjacent territories. Assessment issues are usually considered in accordance with regulatory requirements and involve studying the reservoir's impact on the development of various processes in the coastal zone. For the forecast to be objective, it makes sense to perform it in two stages: the first in the form of a "background" consolidated forecast and the second, in the form of a detailed forecast – after the facility is put into operation in 5 years. This approach will allow taking into account all trends in the development of banks and coastal processes and, if necessary, developing proposals for coastal protection.
Keywords: reservoir; hydroelectric power station; stability; forecast; processing